Penta Helix A Strategy of Development of Womenpreneurs Creative Creations in The City of Tanjungbalai in The Islamic Economic Presfective - Salsabila, Raja Putri; Syahbudi, Muhammad; Ikhsan, Muhammad (SENTRALISASI, 2024)
The aim of this research is to find out suitable development strategies to be carried out by stakeholders in developing creative craft womenpreneurs in Teluk Nibung sub-district. The method used is qualitative with the SOAR method as a determinant of the strategy proposed by the author. The result of the SOAR method is O-A, which is a strategy that uses all opportunities to develop creative seashell crafts. It has been suggested that the development of creative craft womenpreneurs in the city of Tanjungbalai really needs support from the government in the form of capital assistance, marketing and training to increase the potential of the creative economy in the city of Tanjungbalai.